Finite Element Modeling of Cold-Formed Steel Bolted Moment Connection - Muhamad Fauzan Akbari; Data Iranata; Djoko Irawan (Institut Teknologi Sepuluh Nopember, 2022)
This paper describes the finite element procedure for modeling cold-formed steel bolted moment connection to simulate hysteretic moment-rotation behavior and failure mode. The connection element consists of CFS curved flange beams, double-lipped channel columns, and trough plates. Abaqus software is used in this paper. The modeling procedure includes material properties, bolt modeling, boundary conditions, mesh, loading, and geometrical imperfections. The results of the finite element modeling were compared with the experimental test results in the form of a back-bone of the moment-rotation curve and a comparison of failure deformation. It was found that the finite element results had fairly good accuracy in predicting the hysteretic moment–rotation behavior. In the elastic region, the result shows that the finite element model successfully simulates the initial stiffness of the referenced beam-column connection. Meanwhile, the peak moment of the finite element model occurs at the same rotation as the experimental test but the magnitude of the peak moment is lower than the experimental result, which indicates that the finite element model produces a more conservative design. The comparison of failure deformation between finite element model and experimental test shows a very good agreement. The numerical model can simulate well the rotational behavior of the beam-column connection and can predict the general shape and location of local/distortional buckling at the beam-column connection.